2011
DOI: 10.1177/204946371100500303
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Pain Management in Neonates, Infants and Children

Abstract: • Neonates, infants and children all feel pain and require analgesia for painful procedures. • Many painful procedures are associated with medical interventions, including immunisation, heel lance, venesection, IV cannulation and dressing change. • Untreated pain can have short and long term effects, including sensitisation to pain episodes in later life. • A range of non-pharmacological and pharmacological interventions have been shown to be effective for procedural pain management in infants and children, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
0
30
0
2
Order By: Relevance
“…The goal for neonatal pain management ideally is to prevent pain, but if not, that pain should be managed by both non-pharmacological and pharmacological interventions that may even be more effective when they are used in combination. [4,[24][25][26] Understandably, if the knowledge and attitude to neonatal pain management were low, it makes sense the practice would also be low (84.85%). The mean practice percentage was 52.08% with a range of 0% to 95%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal for neonatal pain management ideally is to prevent pain, but if not, that pain should be managed by both non-pharmacological and pharmacological interventions that may even be more effective when they are used in combination. [4,[24][25][26] Understandably, if the knowledge and attitude to neonatal pain management were low, it makes sense the practice would also be low (84.85%). The mean practice percentage was 52.08% with a range of 0% to 95%.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Today we know that neonates experience measurable physiologic and behavioural responses to pain, as demonstrated in shortterm complications, as well as neurologic impairments leading to long-term sequelae. [1,3,4] Also, neonatal pain can be a barrier to parental bonding. [5] It has been shown that both term and preterm infants hospitalised in Neonatal Intensive Care Units (NICUs) experience on average 12 painful medical procedures per day which are mainly left untreated.…”
Section: Introductionmentioning
confidence: 99%
“…These are especially true for infants who are admitted to hospitals and have to undergo many medical procedures, medications, physical and mental exhaustion in an unfamiliar environment. Poor management may result in the child having a phobia towards seeking treatment at the hospital (11). Music is useful as an agent which induces relaxation and reduces anxiety and pain.…”
Section: Resultsmentioning
confidence: 99%
“…Side effects of pain can take a toll on parents especially when their young children become stressful and restless (10). Based on the observations of previous medical experiences, it is noted that every child carries his/her own complex recollection of pain, imagination, worries, and misinterpretation (11). As a result, the child's behaviour can cause family members a lot of anxiety (12).…”
Section: Introductionmentioning
confidence: 99%
“…soočajo z zdravniškimi pregledi, različnimi diagnostičnimi preiskavami in zdravljenjem. Kadar te spremlja bolečina, govorimo o proceduralni bolečini (Wilson-Smith, 2011). Vsi otroci in mladostniki so občasno izpostavljeni bolečim zdravstvenim posegom (npr.…”
Section: Otrokovo Doživljanje Bolečineunclassified